Influence of Connector Width on the Stress Distribution of Posterior Bridges under Loading - S. Mir Mohammad Rezaei; H. Heidarifar; F. Fallahi Arezodar; A. Azary; S. Mokhtarykhoee (Tehran University of Medical Sciences, 2011)
Objective: In all ceramic fixed partial dentures the connector area is a common fracture location. The survival time of three-unit fixed partial dentures may be improved by altering the connector design in regions of maximum tension. The purpose of this study was to determine the effect of buccolingual increase of the connector width on the stress distribution in posterior fixed partial dentures made of IPS Empress 2. To simulate the anatomical condition, we used three-dimensional finite element analysis to generate. Materials and Methods: Three models of three-unit bridges replacing the first molar were prepared. The buccolingual connector width varied from 3.0 to 5.0 mm. Bridges were vertically loaded with 600 N at one point on the central fossa of the pontic, at 12 points along the cusp-fossa contact (50 N each), or at eight points along the cusp-marginal ridge contact (75 N each). Alternatively, a load of 225 N was applied at a 45º angle from the lingual side. Results: Stress concentrations were observed within or near the connectors. The von Mises stress decreased by increasing connector width, regardless of whether the loading was applied vertically or at an angle. Conclusion: Within the limitations of this study, we conclude that increasing the connector width decreases the failure probability when a vertical or angled load is applied.